Stabilization of embankments and coastal bridges with reinforced concrete piles - Mekhmonov Mashkhurbek; Makhamadjonov Shukhratjon; Uralov Akmal (E3S Web of Conferences, 2024)
The article presents the main types of problems in the interface zone of the coastal bridge support with the railway roadbed, the causes of their occurrence. At the transition sections, there is a significant increase in the resulting pressure (Ea) on the shore support of the bridge, under the influence of the train load as a result of an increase in the active soil pressure. The pressures acting on the upper and lower points of the coastal support are determined depending on the height of the embankment, the fictitious height of the train load and the specific gravity of the soil in the transitional sections. The change in the resulting pressure arising from the embankment soils in different soils is calculated on the basis of theoretical calculations and is shown on the graph.